ANALISIS KONFLIK TOKOH UTAMA DALAM NOVEL SERIKAT KEGELAPAN KARYA SIDIK NUGROHO - Seftiani, Seftiani; Syam, Christanto; Seli, Sesillia (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2025)
This research aims to describe the results of conflict analysis of the main characters in the novel Dark Union by Sidik Nugroho. The research method used in this research is a descriptive method in the form of qualitative research. The approach used in this research is a literary psychology approach. The data source for this research is the novel Dark Union by Sidik Nugroho and the data is the main character's conflict in the form of internal conflict and external conflict which includes words, sentences, paragraphs, text discourse or dialogue that leads to the object of analysis. The data collection technique used is a documentary study with the researcher as a data collection tool. Data validity testing techniques are carried out using diligent observation, adequacy of references, and theoretical triangulation. The results of this research show that the main character's internal conflict includes feelings of happiness, feelings of anger, feelings of fear, feelings of confusion, feelings of worry, feelings of love, feelings of sadness, feelings of boredom, and feelings of guilt. The main character's external conflict is divided into two, namely physical conflict and social conflict. The main character's physical conflict involves rain. The main character's social conflicts include threats, corruption, fighting, injustice, vigilantism, murder, rape, and robbery. Researchers have succeeded in designing a learning module using the novel Dark Union by Sidik Nugroho as learning material in schools, especially Indonesian Language and Literature subjects at the even semester class XII high school level.